Police officers killed on duty: Comparing the influence of social investment on line of duty deaths of men and women officers in the United States - Gibbs, Jennifer C. (International journal of police science & management, 2018)
In a unique exploration of line of duty police deaths, Kachurik and colleagues found that police officers in the USA with greater social investment (i.e., officers who were married and had children) were less likely than single officers to be feloniously killed (compared with accidental death) in the line of duty (Kachurik S, Ruiz J and Staub M [2013] Police officers killed on duty: a different view. International Journal of Police Science & Management 15: 114-124). This was confirmed by Gibbs et al. (2014) studying deaths of Baltimore Police Department officers, finding marriage, but not the number of children an officer had, was negatively associated with officer homicide (Gibbs JC, Ruiz J and Klapper-Lehman SA [2014] Police officers killed on duty: replicating and extending a unique look at officer deaths. International Journal of Police Science & Management 16: 277-287). Because marriage and children may have varying effects on each sex, this study explores the relationship between social investment and police officer deaths in the line of duty, comparing men and women officers. With a sample of 4840 men and 207 women police officers in the USA who died in the line of duty between 1980 and 2014, logistic regression confirmed the link between social investment and manner of death—although this relationship presented differently for men and women officers. Specifically, children, but not marriage, significantly influenced the death of women police officers; those who were married at the time of their death were less likely to be killed in the line of duty (compared with accidental death) than unmarried officers, but the number of children had no effect on line of duty deaths for women officers. Marriage had no effect on line of duty deaths for men, although having children increased the odds of a felonious death—which is inconsistent with prior studies. Implications are discussed.